Measures of Bacterial Endotoxins in Gingival Crevicular Fluid and Peripheral Blood of Aggressive Periodontitis Cases—A Clinical Association - Akanksha Kashyap; Brijendra Singh; Srishti Shankar; Atul Gupta; Piyush Gowrav; Mohammad Arif Khan (Journal of Pharmacy and Bioallied Sciences)
Introduction: The present study was undertaken with the objective to evaluate the level of endotoxin produced in the gingival crevicular fluid (GCF) and peripheral blood of subjects with generalized aggressive periodontitis (GAgP) in comparison with periodontally healthy subjects at baseline, three months, and six months post-periodontal surgical treatment. Materials and Methods: A total of 24 subjects aged between 20 and 50 years were selected for the study. They were divided into two groups: generalized aggressive periodontitis (GAgP) subjects (Group A) and periodontally and systemically healthy individuals (Group B). Endotoxin levels were assessed in GCF and peripheral blood of both the groups at baseline, three months, and six months postsurgical treatment. The clinical parameters, such as plaque index (PI), gingival index (GI), probing pocket depth (PPD), and clinical attachment level (CAL), were also recorded at same time intervals. A correlation between the clinical parameters and endotoxin in GCF and peripheral blood was established in diseased cases as compared to healthy individuals. Results: Favorable clinical outcomes with the reduction of PI, GI, PPD, and CAL were achieved for Group A post-surgery when compared to baseline. The GCF endotoxin level in Group A was observed to be significantly higher than Group B and reduced favorably after treatment. In peripheral blood, there was no significant difference in endotoxin level between both the groups. Conclusion: It can be concluded from the results that the level of bacterial endotoxin was significantly raised in GCF, indicating its role in the causation of rapid destruction of the periodontium in aggressive periodontitis subjects.